An Improvement On Learning Quality Of Traditional Songs Through Socio‐Drama Method To The Students Of Grade VII Of RSBI 3 State Junior High School 2 Of Purworejo - Wahyuningsih, Anni; , Prof. Dr. Budi Murtiyasa, M.Kom; , Dra. Siti Zuhriah Ariatmi, M.Hum (2013)
This study aims to know (1) the characteristics of traditional songs learning after being applied to the socio‐drama method on the Seventh Grade Students of State Junior High School 2 of Purworejo; (2) to know whether there is an increase of learning outcome in the traditional songs music after being applied to the sociodrama method on the Seventh Grade Students of State Junior High School 2 of Purworejo. The appropriate research type is a class action research. This study was done using a class action research design that applied two cycles. These cycles consist of four activities, planning the action, implementation, observation, and reflection. Data sources of this study were the event, teachers and students, curriculum, the data of the number and name of students, evaluation result. Benchmark for the success of this research can be seen from the results of the written test. The data were analyzed in a non test (during the learning process) and test (after the learning process). Data validity checking research was triangulation. The results of this study showed that (1) student learning condition that previously passive became more active. Students 'motivation to participate in learning activities has increased, it can be seen from the students' response / attitudes toward instructional media, instructional model, and instructional material that showed a more serious attitude and enthusiasm. (2) Students learning outcome of Class VII RSBI, State Junior High School 2 of Purworejo increased with the application of socio‐drama method. This was evident from the increase in student learning outcomes before and after the given action. Before the given action, the average of student learning outcomes was 73.06 with a percentage of learning mastery of 75%. After being given the action in the first cycle, it increased to an average of 81.25 with a 83.33% percentage of learning mastery. Similarly, in the second cycle also increased an average of 86.88 with a percentage reached 91.67%.